Architectural theories of the environment : posthuman territory - Harrison, Ariane Lourie (New York : Routledge, 2013)
"Humans are the largest environmental force on the planet, making this a new geologic era: The Anthropocene. As architects and designers, we struggle to reconcile the ever increasing environmental, humanitarian, and technological demands placed on our projects. Here, for the first time, editor Ariane Lourie Harrison collects the essays of architects, theorists, and sustainable designers that together provide a framework to help you develop your own guidelines to approaching your work. Each introduction defines a key term, such as biopolitics, animalization, and sociotechnical model, to increase your design vocabulary and highlight themes from the readings. Nine case studies from five countries demonstrate these concepts, so that you can see theory made concrete"--
section 1. Posthuman subjects -- section 2. Posthuman assemblages -- section 3. Posthuman territory.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Architecture -- Environmental aspects; Electronic books